2018
DOI: 10.1021/acs.orglett.7b03631
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Three-Component Reaction of Anilines, Ethyl Vinyl Ether, and Nitro-Paraffin: Assembly of β-Nitroamines

Abstract: A novel palladium-catalyzed amination and nitration of ethyl vinyl ether for the construction of β-nitroamine derivatives under mild conditions has been developed. This transformation provides a new strategy for the installation of amino and nitro from aromatic amines and nitro-paraffin into alkenes. Morpholine resulted in the aza-Henry reaction, while DABCO led to the unexpected rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Jiang and co‐workers introduced a Pd‐catalyzed synthesis of β‐nitroamines from acyclic enol ether, aniline 72 and nitroalkane [43] . In this method, first an imine intermediate has been formed in the existence of Pd‐catalyst via interaction of aniline 72 and ethyl enol ether, followed by the elimination of ethanol.…”
Section: Reactions Of Alkyl Enol Ethersmentioning
confidence: 99%
“…Jiang and co‐workers introduced a Pd‐catalyzed synthesis of β‐nitroamines from acyclic enol ether, aniline 72 and nitroalkane [43] . In this method, first an imine intermediate has been formed in the existence of Pd‐catalyst via interaction of aniline 72 and ethyl enol ether, followed by the elimination of ethanol.…”
Section: Reactions Of Alkyl Enol Ethersmentioning
confidence: 99%
“…Later, the same group developed an elegant Pd‐catalyzed amination and nitration of ethyl vinyl ether for the synthesis of structurally important β ‐nitroamine derivatives (Scheme 10). [24] Different from the classic aza ‐Henry reaction started with imines, this method provides a novel strategy utilizing amines and ethyl vinyl ether as readily available materials in situ generating imine intermediates to form β ‐nitroamines 10‐3 under mild conditions. Several mechanistic experiments of time course were conducted, and the results suggested that 10‐3 could be converted to the β ‐methyl‐ β ‐nitroamine products 10‐4 under this catalytic system.…”
Section: Mono‐/difunctionalization Reactionsmentioning
confidence: 99%